- Kajian Awal Pasir Mineral di Kecamatan Samadua, Aceh Selatan - Bakruddin Bakruddin; Faukas Rahmatillah; Asbahrul Amri (LPPM Politeknik Aceh Selatan, 2021)
A study on mineral sand has been carried out in Samadua District, South Aceh Regency. This study aims to determine the mineral phase and the shape of the surface morphology of the mineral sand. The methods used in this research are XRD and SEM-EDX methods. The XRD analysis results obtained that the SiO2 mineral phase was the highest peak, followed by other mineral phases. While the SEM-EDX test results, visually the surface morphology of the sample is clear that it is dominated by white with Si elements as large as 17.62 wt%, Ca elements as large as 04.30 wt%, and K elements as rough as 02.42 wt%. Based on these results it can be concluded that the phase The dominant constituent minerals in mineral sand are the element SiO2 (Silica).